Sustainable sandwich composites for automotive applications - Jiang, Qihong (Cranfield University, 2022)
The increasing regulation and demand are raising the pressure on manufacturing automotive components towards lighter weight and more recyclability. The commercial road transport industry, contributing a giant part of emissions, is still significantly utilising wood panels as trucks’/ lorries’/ vans’/ buses’ floor or side walls (of boxes), which is cost-effective and used for a very long time. However, with the increasing pressure on lighter weight and more recyclability, the wood panels that could cause deforestation, become a bio- degradable landfill at the end of life and have a relatively high density are no longer the best-fit choice for the floor or side panels of such vehicles. The challenge is to have a floor panel design that could satisfy the increasing pressure and product requirements such as mechanical properties, price, and durability. This research aimed to complete such a challenge by designing sandwich composite structures with fibre-reinforced plastics and foam materials (foam is used in case thermal resistance is needed, and honeycomb materials could be applied when thermal insulating is unnecessary). A fully recyclable sandwich composite achieved using recycled carbon fibre, polypropylene, and recycled PET foam underwent various tests to evaluate its applicability as a commercial transport vehicle floor or side panel. Single fibre tensile tests were operated to understand the behaviour of the RCF mats. Composite mechanical properties were estimated from tensile and three-point bending results, and impact behaviour was analysed after drop tower impact testing. Fibre embedding and sandwich bonding were verified under SEM, and the resulting sandwich composite product properties were also tested using three-point bending. The novelty of such sandwich composite is using RCF with PP to achieve a fully recycled composite skin, while RCF were used mainly with thermoset resin (in the same ways as virgin carbon fibre fabrics). Also, thermoplastic materials such as PP were hard to process with fibre fabrics to form suitable composites due to their non-polar constitution and high viscosity. Fibre fabric would be squeezed together and create a layered structure with fibre rich zone at a very high fibre volume fraction, while the intermedia zone mostly has resins. However, when RCF and PP are mixed, the randomly oriented fibre could also hinder the load from the viscose melt and reduce the amount of fabric pressed closely, forcing some of the melt to pass through inter-fibre areas to create a better filling. Different forms of PP (sheet, powder) were used, and their effect on the compression moulding process and the final product were studied in this research. A faster-pressing cycle was achieved, and a lower pressing pressure was needed for the powder PP process, but disadvantages came from the emission and cost side.
Mills, Andrew - Associate Supervisor
Keywords: Recycled carbon fibre; polypropylene; PET foam; compression moulding; tensile; three-point bending